A3 thinking approach to enhance a complaints handling process in the airline sector - Alshahrani, Bader Mohammed (Cranfield University, 2019)
A prescription for the business success is a matter of concern for company management, researchers and policy makers. There is an ongoing debate regarding the key tools which can increase business efficiency. For example, one stream of research argued that focusing on short-term goals is enough to boost up business performance. On the other hand, another stream argued that companies should focus on long-term performance by emphasising the importance of continuous improvement to assure the delivery of business sustainability. From this point of view, researchers proposed that problem solving is the key for achieving continuous improvement. Problem solving approaches are essential for maintaining the customer service quality as high as possible given the fact that they (problem solving approaches) focus on preventing the reoccurrence of complaints from customers. However, researcher did not reach a consensus regarding the effectiveness of the ‘traditional’ approaches of problem solving (e.g. the 5 whys). As a result, this study develops an A3 Thinking approach for problem-solving in order to enhance the complaints handling process in the airline sector. This approach is validated by using case studies of Saudi Airlines. One of the main advantages of developing such an approach is that it enables the capture of subsequent provision of useful knowledge gained from each complaint, thus enabling the prevention of the reoccurrence of problems, and supporting decision- making. This study provided a valid evidence on the importance of handling customer complaints in different touchpoints during customer journey (pre-flight, on board and post-flight phases). This study found that breaking down customer journey to touchpoints help company management prevent the reoccurrence of customer complaints by increasing the efficiency of responding to customer complaints. The research contributes to the literature by providing a detailed explanation of the journey encountered by airline customers, and it contributes towards enhanced practitioner outcomes by developing a customised A3 Thinking approach for problem-solving in the airline sector based on a learning cycle.
Keywords: A3 thinking; problem-solving approach; complaints handling; airlines; knowledge capturing; knowledge sharing